Narrativas de democratização cultural no Brasil: um olhar sociológico ao Programa Cultura Viva - Rodrigo Manoel Dias da Silva (Ciências Sociais Unisinos)
This article discusses the meanings of cultural democratization explicit in the recent history of the analysis of cultural policies and seeks to ascertain how this conceptual diversification has been expressed in the policies implemented in Brazil. For this purpose, it analyzes the narrative recurrence of these processes in the “Cultura Viva” program of the Ministry of Culture. It concludes that cultural democratization relates to a heterogeneous and multifaceted set of political actions and cultural practices that converge on social objectives whose scale of intervention associates the reallocation of public resources through selection processes of extensive competition, a geographical internalization of the state’s intervention, a pluralization of identity issues and the struggle against social inequalities.